Comparative Dissolution Formulation and Test Simvastatin Ko-Crystal Tablets With Isonicotinamide As Coformer - Sopyan, Iyan; Novianti, Ina; Abdassah Bratadiredja, Marline; Salsabila Hapsari, Raira; Setiawati, Ervina (Universitas Padjadjaran (Unpad), 2024)
Simvastatin is a statin drug used to lower plasma cholesterol in all types of hyperlipidemia. Simvastatin is included in BCS class II with poor solubility. One of the efforts made to increase the solubility of simvastatin is the formation of co-crystals. Co-crystal is a modified type of crystal habit, which consists of two or more molecules in the same crystal lattice. The purpose of this study was to obtain the best excipient combination formula on the simvastatin co-crystalline tablet with isonicotinamide as a coformer and its comparable dissolution test results. The excipient combination optimization was carried out using a two-level factorial method. The optimized Avicel pH 102 and Primogel produced four combination designs on ready-made formulas, namely F1 Avicel pH 102: Primogel (79:2), F2 Avicel pH 102: Primogel (79:8), F3 Avicel pH 102: Primogel (85: 2) and F4 Avicel pH 102: Primogel (85: 8). The evaluation includes evaluating the mass of the print and the quality of the tablets. The excipient combination design solution in the best formula is Avicel pH 102 and Primogel with a ratio (79: 8). The method used in a comparable dissolution test is to compare the values of F1 (difference factor) and F2 (similarity factor) using BootStrap software. The F2 values observed were 50.3 at pH 1.2, 56.09 at pH 4.5, and 59.23 at pH 6.8, which indicates that the simvastatin co-crystalline tablet has similarities with the innovator tablet. The excipient combination design solution in the best formula is Avicel pH 102 and Primogel with a ratio (79: 8). The method used in a comparable dissolution test is to compare the values of F1 (difference factor) and F2 (equation factor) using BootStrap software. The F2 values observed were 50.3 at pH 1.2, 56.09 at pH 4.5, and 59.23 at pH 6.8, which indicates that the simvastatin co-crystalline tablet has similarities with the innovator tablet.Keywords: Simvastatin, co-crystal, two-stage factorial, comparable dissolution test.